2016
DOI: 10.1111/jne.12354
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Responses of the Lateral Hypothalamus to Leptin in Neonatal Rats, and its Implications for the Development of Functional Connections with the Ventral Tegmental Area

Abstract: Food intake is regulated by a close communication between the hypothalamus and the mesocorticolimbic pathways, which are still developing during the perinatal period in the rat, and are known targets for peripheral metabolic hormones such as leptin. A key region for this communication is the lateral hypothalamus (LH), although the onset of leptin responsiveness in the LH is unknown. We examined the activation of cellular signalling molecules in identified LH neurones on postnatal day (PND)10 and 16 and determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…Figure 5 illustrates the changes in pSTAT3 immunostaining in the LHA of PND16 pups following either vehicle or leptin administration in CD and HFD pups. On PND10, there was no significant treatment or diet effect and no treatment X diet interaction on the expression of pSTAT3 immunostaining in the LHA ORX-A field as shown in an earlier study (Gjerde et al, 2016). In contrast, on PND16, HFD pups exhibited significantly higher pSTAT3 activation in response to leptin compared to CD pups.…”
Section: Leptin-induced Pstat3 Activation In Pnd10 and Pnd16 Neonatessupporting
confidence: 50%
See 4 more Smart Citations
“…Figure 5 illustrates the changes in pSTAT3 immunostaining in the LHA of PND16 pups following either vehicle or leptin administration in CD and HFD pups. On PND10, there was no significant treatment or diet effect and no treatment X diet interaction on the expression of pSTAT3 immunostaining in the LHA ORX-A field as shown in an earlier study (Gjerde et al, 2016). In contrast, on PND16, HFD pups exhibited significantly higher pSTAT3 activation in response to leptin compared to CD pups.…”
Section: Leptin-induced Pstat3 Activation In Pnd10 and Pnd16 Neonatessupporting
confidence: 50%
“…One limitation to our study is that in our experiments, retrograde fluorescent microbeads were injected into the region of the LHA containing ORX-A cells, but they may have been taken up by synapses formed with other cell types as well. For instance, we have previously shown that ORX-A neurons are intermingled with Neurotensin neurons in neonates (Gjerde et al, 2016) and thus, microbeads may have been transported by afferent fibers innervating these or other cells in this area.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations